Pengaruh Macam Bahan dan Konsentrasi Compost Tea terhadap Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - Afrizal Hasibuan Hasibuan; Pauliz Budi Hastuti; Ety Rosa Setyawati (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
Abstract— This study aims to determine the effect of the application of various materials and the concentration of compost tea on the growth of oil palm seedlings in the pre-nursery. This research was conducted in Pasar Lembu Village, Air Joman District, Asahan Regency, North Sumatra Province. The study was conducted from March to May 2021. This study used a factorial experimental method arranged in a Completely Randomized Design (CRD) consisting of two factors, namely the various of compost tea material consisting of 3 levels (kascing, cow compost and goat compost) and the concentration of compost tea consisting of 3 levels, namely chemical fertilizers Urea and NPK (as control), 1:3, 1:5, 1:10. From these two factors, 12 treatment combinations were obtained with each treatment repeated 6 times, so that 72 plant samples were obtained. The research data were analyzed by analysis of variance at the 5% level. Significantly different data will be further tested with DMRT (Duncan's Multiple Range Test) at the 5% test level. Parameters observed in this study were plant height, number of leaves, stem diameter, crown fresh weight, shoot dry weight, root fresh weight, root dry weight and root length. The results showed that there was no significant interaction between the various of material and the concentration of compost tea on the growth of oil palm seedlings in the pre-nursery. The various materials of compost tea gave the same effect on all research parameters, as well as the concentration of compost tea. Giving compost tea concentration of 1:10 is more efficient and has been able to replace chemical fertilisers of oil palm seedlings in the pre nursery.